The truth understanding professional networking - Senathirajah, Pathman; VStudios ([S.l.] : VStudios, 2008)
Pathman Senathirajah talks straight in this no-nonsense video about the black and white truths of network marketing. He extols the value of not just doing good business, but doing good business the right way. Empowering, enlighting and encouraging, this video will open your eyes to the truth about the company, its goals, its systems and how you can do your part as a member of the V
Title from title screen
DVD format
Keywords: Multilevel marketing; Direct marketing